Concurrent Stenoocclusive Disease of Intracranial and Extracranial Arteries in a Patient with Polycythemia Vera - Le H. Hua; Robert L. Dodd; Neil E. Schwartz (Case Reports in Medicine)
Moyamoya disease is a stenoocclusive disease involving the intracranial carotid and proximal middle cerebral arteries. There are rarely any additional extracranial stenoses occurring concurrently with moyamoya. The pathophysiology of moyamoya remains obscure, but hematologic disorders, notably sickle-cell anemia, have been associated in some cases. We describe the novel case of polycythemia vera associated with severe steno-occlusive disease of both intracranial and extracranial large arteries. A 47-year-old woman with polycythemia vera had multiple transient ischemic attacks, and noninvasive vessel imaging revealed steno-occlusive disease of bilateral supraclinoid internal carotid arteries with moyamoya-type collaterals, proximal left subclavian artery, right vertebral artery origin, bilateral renal arteries, superior mesenteric artery, and right common iliac artery. Laboratory workup for systemic vasculitis was negative. She required bilateral direct external carotid to internal carotid bypass procedures and percutaneous balloon angioplasty of her right VA origin stenosis. This case suggests that hematologic disorders can lead to vessel stenoses and occlusion. The pathophysiology may be due to a prothrombotic state leading to repeated endothelial injury, resultant intimal hyperplasia, and progressive steno-occlusion.